Analysis of the Effect of Maternal Perception on Completeness of Child Immunization Status with Health Belief Model - Yessica Eka Puri; Bhisma Murti; Argyo Dermatoto (Journal of Health Promotion and Behavior, 2016)
Background: Child immunization coverage was low in several health centers in Surakarta, Central Java. Some of the health centers did not achieve GAIN Universal Child Immunization (UCI) target in 2014. For example, Penumping Health Center (HBV <7 days= 86.9%, BCG= 87.8%, Campak= 87.5%, DTP-HBV-HIB= 86.7%, Polio= 87.5%) and Banyuanyar Health Center (Campak= 89.6%). This study aimed to determine the effect of maternal perception on completeness of child immunization status using Health Belief Model (HBM).Subjects and Method: This was an analytic observational study with case control design. It was conducted at Penumping and Banyuanyar Health Centers, Surakarta, Central java. A total sample of 120 mothers and their respective children aged <9 years was selected for this study by fixed disease sampling. This sample consisted of children with complete immunization and the other children with incomplete immunization (ratio= 1:4). The dependent variable was completeness of immunization status. The independent variables were maternal perception on various HBM constructs, including perceived susceptibility, seriousness, threat, benefit, and barrier. The data were collected by a set of questionnaire, and analyzed by path analysis.Results: Perceived susceptibility had indirect and positive effect on completeness of immunization status via perceived threat, although it was not statistically significant (b= 0.63; 95% CI= -0.13 to 1.39; p= 0.104). Perceived seriousness had indirect positive and statistically significant effect on completeness of immunization status via perceived threat (b= 1.10; 95% CI =0.71 to 3.04; p=0.005). Perceived threat (b= 1.88; 95% CI= 0.34 to 1.86; p= 0.002), and perceived benefit (b= 1.83; 95% CI = 0.69 to 2.96; p= 0.002), showed direct positive and statistically significant effect on completeness of immunization status. Perceived barrier had direct and negative effect on completeness of immunization status  (b= -0.96; 95% CI= -1.97 to 0.05; p= 0.063).  Conclusion: Maternal perception on child susceptibility, disease seriousness, disease threat, benefit and barrier of immunization, have effects on the completeness of immunization status.Keywords: immunization status, completeness, health belief modelCorrespondence: Yessica Eka Puri. Masters Program in Public Health, Sebelas Maret University, Surakarta. Mobile: 087856408766.Journal of Health Promotion and Behavior (2016), 1(3): 211-222https://doi.org/10.26911/thejhpb.2016.01.03.08